Evaluating the Effects of Cooking on the Decrease Microbial Contamination of kebabs and Hamburgers Supplied for Selling in Southern Areas of Tehran - Norooz Babaei H; Salsali M; Zeraati H; Vahedi S; Soltan Dallal MM; Kaffashi T; Arasteh M (Tehran University of Medical Sciences, 2007)
Introduction and objectives: Despite the advances in the control of food-borne diseases, still one of the dilemmas in the health of most societies and a matter of concern for health authorities is food poisoning and food-borne diseases by unsafe foods.Materials and methods: In total 390 samples, including 195 samples of raw kebabs and hamburgers and 195 samples of the cooked ones were gathered from shops, sampling raw and cooked meat at the same time, and they were sent to the laboratory for testing, over a period of one year. The methods used for the tests were based on the Iranian National Standard procedures, numbers 356 and 2394.Results: All the cooked specimens had bacterial contamination in acceptable standard levels and therefore were considered consumable. From the 165 raw kebab samples, 90 samples (54.5%) were consumable but 75 samples (45.5%) were not fit for consumption, where from 30 raw hamburger samples, 22 samples (73.3%) were consumable and 8 (26.7%) were inconsumable. In serological evaluations, Thompson serotype had the highest prevalence in kebab and hamburger samples.Conclusion: The results of present study show that there is no reason for concern in consuming cooked kebabs.